Pengaruh kepemimpinan dan komunikasi terhadap produktivitas karyawan pada PT. Perkebunan Nusantara V Tanah Putih Rokan Hilir - Simanjuntak, Leni Suriyani; Ningsih, Dewita Suryati; Fitri, Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted on PT. Perkebunan Nusantara V Tanah Putih Rokan Hilir in order to determine the influences of Work Leadership and work communication either simultaneously or partially on Employee Productivity in PT. Perkebunan Nusantara V Tanah Putih Rokan Hilir.Total sample of 74 respondents on PT. Perkebunan Nusantara V Tanah Putih Rokan Hilir. The sampling technique used is stratified random side and Path analysis method by using SPSS version 20. Simultaneous regression (F test) showed that the independent variables studied (Work Leadership and Work Communication) together (simultaneously) have a significant influence on the dependent variable (employee Productivity). The magnitude of the influence that (R2) by the two independent variables together against the dependent variable, while the remaining is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables that Work Leadership doesn’t give significant influence on employee Productivity. work communication have significant influence on employee work productivity, and together have a significant effect on the productivity of employees and work leadership significantly influence employee productivity via work communication. So from the results of this research in employee productivity variables that must be improved is the Completion of work on time, the leadership variables that must be improved is the essence of giving exemplary, whereas the communication variables that should be improved is the attitude of supporting structures such as creating an easy flow of communication between fellow employees contacted by employees and leaders.Keywords: Work Leadership, Work Communication, Employee Productivity.